2022
DOI: 10.3390/children9060849
|View full text |Cite
|
Sign up to set email alerts
|

Scoping Review of Yoga in Schools: Mental Health and Cognitive Outcomes in Both Neurotypical and Neurodiverse Youth Populations

Abstract: Yoga is used widely as a therapeutic tool for physical and mental well-being. The mind-body activity could be an inclusive and cost-effective intervention used within schools to help tackle the mental health crisis in youth populations. To date, research has focused on mainly neurotypical youth populations. However, greater acknowledgement of the impact for neurodiverse youth populations is warranted. Therefore, the aim of this scoping review is to understand what is known about the relationships between yoga … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 86 publications
(311 reference statements)
0
5
0
Order By: Relevance
“…A recent scoping review reported evidence of positive effects of school-based yoga programs on academic performance in neurotypical as well as neurodiverse populations (Hart et al., 2022). However, the yoga condition in our design did not result specifically in increased pseudoword learning for children who are DHH after one session.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent scoping review reported evidence of positive effects of school-based yoga programs on academic performance in neurotypical as well as neurodiverse populations (Hart et al., 2022). However, the yoga condition in our design did not result specifically in increased pseudoword learning for children who are DHH after one session.…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity is associated with increased learning in general (Hart et al, 2022;Loprinzi et al, 2023;Robinson et al, 2023;Roig et al, 2013;Winter et al, 2007), and with increased word learning in particular (Lund et al, 2020;Mavilidi et al, 2015;Salis, 2013;Schmidt-Kassow et al, 2014). Often this physical activity is conceptualized as a break in the cognitive task of learning; for example, in a review paper, Mahar (2011) reported that short physical activity breaks resulted in a small to moderate increase in attention-on-task in school-age children.…”
Section: General Physical Activitymentioning
confidence: 99%
“…For example, de Oliveira (2020) within their scoping review of yoga and emotional-social intelligence in children and youth, concluded yoga may be of significant value in supporting emotional, social intelligence, development among youth presenting with a variety of issues such as social and behavioral problems, substance abuse, autism, trauma, obesity, ADHD and other psychiatric conditions. Conversely, Hart et al (2022) aimed to map out the relationship between yoga in schools and mental health and cognition among the neurodiverse and neurotypical youth populations. They found that despite a diversity in school-based yoga programs examined, there was clear evidence supporting the benefits of yoga in schools.…”
Section: Benefit Of Yoga For Childrenmentioning
confidence: 99%
“…Yoga practice includes participation in physical postures (asanas), breathing techniques (pranayama), and meditation practices ( Govindaraj et al, 2016 ). Research has demonstrated the effectiveness of school-based yoga programs for Indian children and youth in improving mental health and cognitive performance ( Kauts & Sharma, 2009 ; Singh, 2018 ; Hart et al, 2022 ; Telles et al, 2014 ). Yoga practice also enhances the musculoskeletal system, including improving muscle strength, manual dexterity, and grip strength ( Raghuraj & Telles, 1997 ; Mandanmohan et al, 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…Given the rising global prevalence of yoga, it is important to understand yoga’s association with moderate-to-vigorous physical activity (MVPA), a key determinant in NCD prevention ( CDC, 2022 ; 24-Hour Movement Guidelines, n.d ; Participaction, 2022 ). Current research on the effects of yoga on children and youth has been notably limited, especially considering that it is a culturally-appropriate intervention that could significantly benefit Indian children and youth ( Kauts & Sharma, 2009 ; Singh, 2018 ; Hart et al, 2022 ; Telles et al, 2014 ). Thus, this study aims to investigate the association between yoga practice and MVPA among children and youth in India, while controlling for sociodemographic and related contextual factors, to inform culturally-appropriate physical activity interventions.…”
Section: Introductionmentioning
confidence: 99%